Effect of Robot-Assisted Therapy on Participation of People with Limited Upper Limb Functioning: A Systematic Review with GRADE Recommendations - Fernanda M. R. M. Ferreira; Maria Emília A. Chaves; Vinícius C. Oliveira; Jordana S. R. Martins; Claysson B. S. Vimieiro; Adriana M. V. N. Van Petten (Occupational Therapy International)
Background. Previous studies have suggested that robot-assisted therapy (RT) is effective in treating impairment and that it may also improve individuals’ participation. Objective. To investigate the effect of RT on the participation of individuals with limited upper limb functioning (PROSPERO: CRD42019133880). Data Sources: PEDro, Embase, MEDLINE, CINAHL, Cochrane, AMED, and Compendex. Inclusion Criteria. We selected randomized or quasirandomized controlled studies comparing the effects of RT with minimal or other interventions on participation of individuals with limited upper limb functioning. Data Extraction and Synthesis. Methodological quality of the included studies was assessed using the 0-10 PEDro scale, and effect estimates were reported using standardized mean differences (SMDs) with 95% confidence intervals (CIs), and the certainty of the current evidence was assessed using the GRADE. Results. Twelve randomized controlled studies involving 845 participants were included. The estimates of medium effects between RT and minimal intervention (MI) at a short-term follow-up were pooled, but there are no short-term effects between RT and OI. Standardized differences in means were as follows: 0.6 (95% CI 0.1 to 1.2) and 0.2 (95% CI -0.0 to 0.4). There were also no effects of additional RT in the short- or medium-term follow-up periods. Standardized differences in means were as follows: -0.6 (95% CI -1.1 to -0.1) and 0.2 (95% CI -0.3 to 0.8). The methodological quality of the included studies potentially compromised the effect estimates of RT. The existing evidence was very low-quality with many confounding variables between studies. Conclusions. For patients with upper limb neurological dysfunction, low-quality evidence supports RT over MI in terms of improving individual participation in the short term. The existing low- to very low-quality evidence does not support RT over OI in either the short- or medium-term follow-up periods with respect to community participation.